PENGARUH PENERAPAN MODEL PEMBELAJARAN ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION (ARIAS) BERBANTUAN BAHAN AJAR BERMUATAN NILAI KARAKTER TERHADAP KOMPETENSI SISWA KELAS XI SMAN 13 PADANG - Tri Agunaisy; Yenni Darvina; Murtiani Murtiani (Universitas Negeri Padang, 2016)
Students’ achievement by second grade of SMA 13 Padang will be optimum if the teacher use a learning model that can assure students towards their ability in learning. One of learning model that can be used is Assurance, Relevance, Interest, Assessment, and Satisfaction (ARIAS) which learning materials have character values in it. This research aims to research the impact of ARIAS learning model which have character values towards competence of the second grade students SMAN 13 Padang. This research used Quasi Experiment Research with Randomized Control Group Only Design. The sample in this research was taken by Purposive Sampling Technique. The instruments of this research were observation sheet for behavior competence, writing test for knowledge competence, and rubric score for skill competence. The hypothesis was tested by using Chi Square test for the behavior and skill competences; meanwhile t-test was used to test the knowledge competence. The results revealed that ARIAS learning model can increase students’ competences of second grade at SMAN 13 Padang in behavior and skill competences, but this model did not give impact for skill competence, with significance level 0.05